The Relationship between Teaching Instructions and Students’ Achievement in Tilawah al-Quran among Form Two Students in Malaysia - Che Noh, Mohd Aderi (2008)
The main purpose of the study was to explore the relationship between the teaching instructions and students’ achievement in Tilawah al-Quran in Malaysia. This study also attempted to investigate the variables that have significant relationships with teaching instructions and students’ achievement in Tilawah al-Quran. This study was also aim to identify the main variables that contributed to the teaching instructions and students’ achievement in Tilawah al-Quran. Finally, this study will produce a Model Peningkatan Tilawah al-Quran. 257 teachers and 1651 students from secondary schools in Malaysia were selected by stratified and cluster samplings. A set of questionaire was developed by the researcher and the reliability indexes of Alpha Cronbach were between 0.6083 to 0.9587. Descriptive statistics of frequencies, percentages, mean and standard deviation were used to answer the research questions. Inferential statistics of correlation, Linear Regression, Multiple Regression, Confirmatory Factor Analysis and Structural Equation Modelling were used to test the research hypotheses. The overall findings of the study indicated that the teaching instructions was at the moderate level. However, teachers’ attitude towards Tilawah al-Quran was at the highest level. Furthermore, students’ attitude towards Tilawah al-Quran was at the highest level meanwhile learning behaviour and learning surroundings in Tilawah al-Quran was at the moderate level. Correlation analysis highlighted that there was a significant relationship between teaching experience and teaching instructions with r = 0.140. There was a significant relationship between teachers’ attitude and teaching instructions with r = 0.591. There was also a significant relationship between students’ attitude and teaching instructions with r = 0.383. Moreover, there was a significant relationship between students’ learning behaviour and teaching instructions in Tilawah al-Quran with r = 0.410. There was a significant relationship between students’ attitude and students’ acievement with r = 0.179. Next, there was a significant relationship between students’ learning behaviour and students’ achievement in Tilawah al-Quran with r = 0.170. In addition, there was a significant relationship between students’ learning surrounding and students’ achievement r = 0.119. Finally, there was a significant relationship between teaching instructions and students’ achievement in Tilawah al-Quran with r = 0.067. Linear Regression analysis showed teachers’ attitude and teaching experience contributed 37.3% to teaching instruction. Meanwhile students’ attitude and learning behaviour contributed 21.2% to teaching instruction. The study indicated that students’ attitude, learning behaviour, learning surroundings contributed 4.1% to students’ achievement in Tilawah al-Quran. The study found that teaching instruction contributed 0.4% to students’ achievement in Tilawah al-Quran. Lastly, Multiple Linear Regression analysis showed that students’ attitude, learning behaviour, learning surroundings and teaching instruction contributed 4.1% to students’ achievement in Tilawah al-Quran. Confirmatory Factor Analysis showed that Model Peningkatan Tilawah al-Quran based on the process factor that involved eight indicators. Two indicators were from component starting teaching, four indicators were from component extending teaching, one indicator was from component closing teaching and lastly one indicator was from component teaching aids. Meanwhile, based on the students’ input factors, Model Peningkatan Tilawah al-Quran clearly shown by variable of attitude with two indicators, variable of learning behaviour with three indicators and variables learning surroundings with three indicators. Structural Equation Modelling analysis showed that Model Peningkatan Tilawah al-Quran contributed by students’ attitude varians 56%, learning behaviour varians 84% and learning surroundings varians 90%. Furthermore, students’ achievement varians in Tilawah al-Quran was influenced by all three factors namely students’ attitude towards Tilawah al-Quran, learning behaviour and learning surroundings 4%. The findings from the study could guide teachers on the importance of teaching instructions, teachers’ input factors such as teaching experience and teachers’ attitude toward Tilawah al-Quran to ensure students’ achievement in Tilawah al-Quran. Futhermore, the study provided an empirical basis to describe the correlation between input, process and product factors. The study also showed that the importance of components in teaching instructions should be focused in order to maximise students’ achievement in Tilawah al-Quran. Furthermore, the students’ achievement in Tilawah al-Quran was not only influenced by teaching instructions in school, but also by students’ factors such as students’ attitude, learning behaviour and learning surroundings influenced by parents and community to produce the generation of celik al-Quran.